1993
DOI: 10.1002/ijc.2910550426
|View full text |Cite
|
Sign up to set email alerts
|

Role of cell cholesterol in modulating vincristine uptake and resistance

Abstract: The relationship between cell-membrane permeability to vincristine and cholesterol/phospholipid levels was studied in L5178Y murine leukemic lymphoblasts and in 2 multidrug-resistant cell sublines, VCR/P60 and VCR/P200, which expressed increasing levels of vincristine resistance. The uptake of 3H-vincristine was measured in all cell lines and in cholesterol-depleted and -reloaded L5178Y and VCR/P200 cells. The initial rate of drug entry in resistant cells was lower than that measured in the parental cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
1
23
1
1
Order By: Relevance
“…In contrast to these results, Pallarés-Trujillo et al (1993) reported an influence of cholesterol on cellular permeability to the P-glycoprotein substrate vincristine not only in multidrug-resistant but also in sensitive cells, indicating an unspecific modulation of the permeation of vincristine through the plasma membrane by cholesterol. However, the experimental design as well as the investigated substrate and the cell lines were not identical, making a direct comparison impossible.…”
contrasting
confidence: 77%
“…In contrast to these results, Pallarés-Trujillo et al (1993) reported an influence of cholesterol on cellular permeability to the P-glycoprotein substrate vincristine not only in multidrug-resistant but also in sensitive cells, indicating an unspecific modulation of the permeation of vincristine through the plasma membrane by cholesterol. However, the experimental design as well as the investigated substrate and the cell lines were not identical, making a direct comparison impossible.…”
contrasting
confidence: 77%
“…Similarly, cholesterol derivatives ("rigidifiers") caused a ϳ1.6-fold maximum increase in rhodamine 123 retention (45). In contrast, vincristine retention (or "influx") was inversely correlated with cholesterol concentration in the membrane (46), and known fluidizers inhibited DNR transport in canalicular membrane vesicles (47). Membrane environment alterations caused by cholesterol are known to affect P-gp interaction (48) with substrates such as azidopine, whose binding increases by ultimately 3-fold at 20% cholesterol in liposomes before decreasing at higher concentrations (49).…”
Section: Discussionmentioning
confidence: 94%
“…Many chemoresistant cell lines show a modification in their plasma membrane lipid content. [15][16][17][18][19][20][21] Cholesterol is one of the lipids known to be abundant in chemoresistant cell membranes. [15][16][17][18][19][20][21] Interestingly, total cholesterol content was greatly increased in both R1 and R2 cell lines as illustrated in Figure 7.…”
Section: Role Of Caveolin-1 In Etoposide Resistance Development In A5mentioning
confidence: 99%
“…Cholesterol was shown to stimulate the ATPase activity of p-glycoprotein. [15][16][17][18][19][20][21] Caveolins could then be a marker for plasma lipid changes, a facilitating factor in the development of drug resistance than playing a direct role in this process.…”
Section: Wwwlandesbiosciencecom Cancer Biology and Therapy 957mentioning
confidence: 99%
See 1 more Smart Citation